Analysis of operation efficiency and carbon emission of quasi Class Ⅳ upgrading and reconstruction of a sewage treatment plant - YU Bo; MA Jiao; LI Xiaoning; SHEN Pengfei (Gongye shui chuli)
In order to meet the requirements of sewage treatment capacity and treatment standards, a sewage treatment plant in Shandong was upgraded and reconstructed based on the Class A water quality standard of “Pollutant Discharge Standards for Urban Sewage Treatment Plants” (GB 18918-2002). The advanced treatment process of “high efficiency sedimentation tank+denitrifying deep bed filter” was adopted, and the sewage treatment facility of “pretreatment+AAO+high efficiency sedimentation tank+denitrifying deep bed filter+ultraviolet/sodium hypochlorite disinfection” with a scale of 60 000 m3/d was expanded. The pollutant removal efficiency and carbon emission distribution during sewage treatment process before and after renovation were analyzed. The results showed that the removal effect of pollutants was further strengthened and consolidated after the transformation, and the average effluent TN and TP were 7.09 mg/L and 0.06 mg/L, respectively, and the removal rates of TN and TP reached 94.7% and 99.1%, respectively. The effluent quality(except TN) reached the Class Ⅳ standard of the Environmental Quality Standards for Surface Water(GB 3838-2002). CH4 contributed the most to carbon emission before and after the transformation. After the transformation, the proportion of electricity consumption in the overall carbon emission increased by 16.49%, while the carbon emission generated by the consumption of water agent decreased by 27.69%, from 0.585 kg/m3 to 0.423 kg/m3.